Positive Psychology: Seeing Work-Life Balance as Positivity Value from Millenials Perspective - Narendra Jagat Pramana; Silvia Saputra; Dara Delila; Cholichul Hadi (Jurnal Syntax Admiration, 2024)
The necessity to oversight numerous positive organizational phenomena gave rise to positive organizational psychology. The nature of job relationship has drastically changed over the past decades, affecting not just the sort of labor performed but also when and how much it is completed. Many people today perform a variety of jobs, including part-time jobs, temporary jobs and several occupations. In addition, as more people work several jobs, there is a corresponding rise in the amount of overtime that these people put in. The individual’s capacity to balance their work and personal lives has drawn a lot of study attention and is a real concern for both individuals and organization. Millenial generation interact with older generations in different ways. The millenial generation matures and becomes more adaptable to new situations and all potential outcomes, which is why it is frequently referred to be a generation that is particularly comfortable with chage. Compared to the previous generation, the millenials worker gives work-life balance more consideration. Stress and burnout at work are the consequences of an unbalanced work-life. This study used literature review method by collecting data through several literatures and journals related to positive psychology, the concept of positivity, work-life balance and millenials. Data gathering using automated searches on sites like Research Gate, Google Scholar, and Sage Journal. This research uses 9 scientific articles as a data source. The result of this study is to understand how the millenials perspective seeing work-life balance as a positive value in a company. This study examines millenials perceive the implementation of work-life balance in the workplace positively. Companies can utilize this information to effectively acquire millenials talent and employ the best resources to entice this type of potential.